Effects of compositions of filler, binder and porosity on elastic and fracture properties of nuclear graphite - Sun, Wei (Elsevier, 2015)
Physical mechanisms at different length scales have to be taken into account while predicting the overall failure of nuclear graphite structures of advanced gas cooled graphite reactors. In this paper, the effect of composition of meso graphite phases and porosity on the aggregate elastic properties is predicted using the Eshelby homogenisation method. Results indicate an overall decrease in elastic modulus with an increase in porosity. Subsequently, the moduli at different porosity levels are used to predict the critical strain energy release rates for crack propagation of graphite, and fracture behaviour is studied using compact tension and four point bending tests. Compared to flexural strength at zero porosity level, significant reduction in strength of up to 80% at 30% porosity level is observed. Evolution of flexural strength due to porosity is also compared against available experimental values of graphite from UK nuclear plants.